2010
DOI: 10.1590/s1516-89132010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacteria contaminating alcoholic fermentations by killer yeasts

Abstract: The aim of this work was to study the in vitro antibacterial activity possessed by killer yeast strains against bacteria contaminating alcoholic fermentation (Bacillus subtilis, Lactobacillus plantarum, Lactobacillus fermentum and Leuconostoc mesenteroides), in cell X cell and cell X crude toxin preparations. The bacteria were not inhibited by any S. cerevisiae killer strains (5 out of 11). The inhibition caused by two crude toxin preparations (Trichosporon figueirae and Candida sp) against L. plantarum was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The mechanism associated with this inhibition is quite controversial. Some authors have reported that the killer phenomenon, which had previously been limited to yeastyeast interaction, might occur between yeast and bacteria, noting that killer strains are capable of inhibiting the growth of bacteria such as E. coli, S. aureus, L. monocytogenes, and Klebsiella oxytoca (Bajaj, Raina, & Singh, 2013;Leverentz et al, 2006;Meneghin, Reis, & Ceccato-Antonini, 2010;Polonelli & Morace, 1986). However, it has been suggested that S. cerevisiae produces substances with AA against malolactic bacteria and that one of these substances has lysozyme characteristics (Dick, Molan, & Eschenbruch, 1992).…”
Section: Evaluation Of Cell Viability Of Bacteriamentioning
confidence: 99%
“…The mechanism associated with this inhibition is quite controversial. Some authors have reported that the killer phenomenon, which had previously been limited to yeastyeast interaction, might occur between yeast and bacteria, noting that killer strains are capable of inhibiting the growth of bacteria such as E. coli, S. aureus, L. monocytogenes, and Klebsiella oxytoca (Bajaj, Raina, & Singh, 2013;Leverentz et al, 2006;Meneghin, Reis, & Ceccato-Antonini, 2010;Polonelli & Morace, 1986). However, it has been suggested that S. cerevisiae produces substances with AA against malolactic bacteria and that one of these substances has lysozyme characteristics (Dick, Molan, & Eschenbruch, 1992).…”
Section: Evaluation Of Cell Viability Of Bacteriamentioning
confidence: 99%
“…Finally, killer yeasts may also inhibit wine-related, as well as human pathogenic, bacterial species (Bajaj et al, 2013;Meneghin, Reis, & Ceccato-Antonini, 2010;Oliva-Neto, Ferreira, & Yokoya, 2004). Some killer toxins have been shown to be active and stable at pH, temperature and nutritional conditions found in winemaking process, enough to cause sluggish or even stuck fermentations (Carrau, Neirotti, & Gioia, 1993;van Vuuren & Wingfield, 1986).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…2B). Several authors have reported the inhibitory effect of non-Saccharomyces killer yeast supernatants on different bacterial groups, mainly gram positive bacteria [14][15][16].…”
Section: Inhibitory Effect On Wine Labmentioning
confidence: 99%